Antara Interaksi Budaya dan Dakwah Kajian Novel Ayat Ayat Cinta - Siti Zubaedah (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
The article discusses the interation of religion and culture in the novel Ayat-ayat Cinta. This novel depicts human episode of a particular nuance in the context of interculturalism. It reveals undetailed cultural elements to a tendency of presenting  the culture of ’normative Islam’. The novel’s spirit leads to hegemonize certain  cultural aspect presented the religion of Islam.